Challenges Facing Teenage Mothers in School, Teachers’ Perspective: The Case of WA West District - Adangabe , Amos Amuribadek (South Asian Journal of Social Sciences and Humanities, 2020)
Bearing children as a young teenager is normally connected with various interruptions for young ladies with regards to class participation. The young mothers’ who are in school are left to unwind the interruptions some of the time all alone. Denying them the help they have to seek after their schooling sentence them and their infants to an endless loop of neediness and obliviousness. In the event that society anticipates that the young ladies should be effective with tutoring, there must be arrangement that objectives their exceptional instructive requirements. The study explored the perception of educators about the difficulties confronting adolescent moms in school in the WA West District. The purposeful sampling technique was used in selecting the teachers involved. A focused group discussion was used in gathering and data analysis was done thematically. While the results indicate that, majority of the teenage mothers in school are mostly tired even before they come to school, it further revealed that the majority of the teachers perceive teenage mothers having low self-esteem, poor time management, role conflict and how they are supported were among the things discussed. The recommendations to tackle these perceptions were made.